2022
DOI: 10.1186/s12909-022-03259-0
|View full text |Cite
|
Sign up to set email alerts
|

How medical students co-regulate their learning in clinical clerkships: a social network study

Abstract: Background Self-regulated learning is a key competence to engage in lifelong learning. Research increasingly acknowledges that medical students in clerkships need others to regulate their learning. The concept of “co-regulated learning” captures this act of regulating one’s learning by interacting with others. To effectively cultivate such skills in students, we need to increase our understanding of co-regulated learning. This study aimed to identify the purposes for which students in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…In this research, we observed a reduced trust of some students in their peers' (developing) expertise. The same-level peers they use for co-regulated learning during their Bachelor's, are typically replaced with clinical supervisors during their Master's program, as is also shown in other research [19,35]. This could be attributed to the fact that students are a part of a community of learners [36,37] during their Bachelor's program, and that when they enter clinical practice they feel the need to take part in that speci c community of practice with the medical specialist at the center [33,34].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In this research, we observed a reduced trust of some students in their peers' (developing) expertise. The same-level peers they use for co-regulated learning during their Bachelor's, are typically replaced with clinical supervisors during their Master's program, as is also shown in other research [19,35]. This could be attributed to the fact that students are a part of a community of learners [36,37] during their Bachelor's program, and that when they enter clinical practice they feel the need to take part in that speci c community of practice with the medical specialist at the center [33,34].…”
Section: Discussionmentioning
confidence: 82%
“…Whereas PAL is widely used in the preclinical teaching of medical students, recent literature states that PAL is particularly useful to students in the clinical stages of their education where the clinical-reasoning learning process accelerates [6,18]. Nevertheless, there is a notable decline in the extent to which students use each other for their own learning processes during clinical clerkships compared to the preclinical years [19]. Nowadays, the current generation of students is characterized by a stronger individualistic orientation compared to their predecessors [20].…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados de nuestro estudio coinciden con los encontrados por Bransen et al (2022) quienes confirmaron la importancia de los pares en el aprendizaje en clínicas de los estudiantes y cómo las redes de relaciones que se establecen en las prácticas clínicas refuerzan la autorregulación del aprendizaje y el aprendizaje de habilidades. También, el estudio de Atman y Yildiz (2022), ya mencionado, señaló la influencia de la motivación del estudiante en su autonomía y cómo un ambiente colaborativo de aprendizaje influye en la regulación de la motivación de los estudiantes universitarios, así, estrategias de planificación, seguimiento y autorregulación pueden ser fuerzas impulsoras de la autonomía del estudiante en las actividades de aprendizaje colaborativo.…”
Section: Discussionunclassified
“…This not only promotes SRL but embodies the ideals of coregulated learning, in which social influences (e.g., a supervisor's expertise) help to shape the learner's approach. 21,22 A nonspecific goal such as "being more efficient" could be followed up with questions about perceived areas of inefficiency. This may then lead to an opportunity to discuss strategies for workflow management that can then be directly observed and serve as the basis for feedback in the moment or after shift.…”
Section: Barrier S and P Oss Ib Le Soluti On Smentioning
confidence: 99%